Modified Role-play to Improve Speaking Output: A Classroom Action Research - Prastiwi, Chyntia Heru Woro (MAGISTRA, 2016)
Students of senior high school as intermediate learners still speak unconfidently and not fluently.They had not been prepared for spontaneous communication and could not cope with all of its simultaneousdemands. In fact, studentsâ daily communication remains spontaneous and interactional. The need to improvethe spoken English of Islamic Senior High School students prompted Classroom Action Research by implementingmodified role-play. This strategy provides opportunities for meaningful communicative behavior about relevanttopics by using learner-learner interaction. The students who worked in pairs were the sources for scenario ofrole-play. The scenarios were exchanged inter group. Each group played the scenario of the other groups andit was recorded. Analysis showed that students speaking ability got improvement through modified role-play.They passed the criteria of success, they were more confident in speaking spontaneously, and their communicativecompetences got betterment, including the competences of sociolinguistic, strategic, discourse, fluency, andaccuracy. It was recommended, therefore, that English teachers consider this technique in teaching speaking.Keyword: Role-play, Classroom, Research